Numerical study on ship-generated unsteady waves based on a Cartesian-grid method - Yang, Kyung-Kyu; Kashiwagi, Masashi; Kim, Yonghwan (Journal of hydrodynamics. Series B, 2020)
The added resistance of a ship in waves can be related to ship-generated unsteady waves. In the present study, the unsteady wave-pattern analysis is applied to calculate the added resistance in waves for two modified Wigley models using a Cartesian-grid method. In the present numerical method, a first-order fractional-step method is applied to the velocity-pressure coupling in the fluid domain, and one of volume-of-fluid (VOF) methods is adopted to capture the fluid interface. A ship is embedded in a Cartesian grid, and the volume fraction of the ship inside the grid is calculated by identifying whether each grid is occupied by liquid, gas, and solid body. The sensitivity to the location of measuring position of unsteady waves as well as the number of solution grids is examined. The added resistance computed by direct pressure integration and wave pattern analysis is compared with experimental data. In addition, nonlinear characteristics of the added resistance in waves are investigated by detailed analyses of unsteady flow field and resulting wave pattern.